Layer‐by‐Layer Processed Organic Photovoltaic Cells Using Slot‐Die‐Coating Methods and Non‐halogenated Solvents under Ambient Conditions with PCE of 10% - Pandeng Li; Anderson Hoff; Akpeko Gasonoo; Muhammad R. Niazi; Maryam Nazari; Gregory C. Welch (Advanced Materials Interfaces, 2023)
Abstract Laboratory‐controlled conditions, spin‐coating method, and non‐ecofriendly halogenated solvents that have been employed for higher‐performance organic solar cells (OSCs) are not compatible with large‐scaled, roll‐to‐roll (R2R) manufacturing in ambient conditions. Slot‐die coating is a viable upscaling method, but the investigation of slot‐die‐coated OSCs is still rare, especially OSCs with all functional layers deposited with non‐halogenated solvents in air. Herein, all slot‐die coated devices are successfully manufactured by sequentially slot‐die coating the hole transport layer (PEDOT:PSS), the photoactive layers (PM6 and BTP‐4F‐12 (Y6‐C12)), and the electron transport layer (PFN‐Br). Because of solubility variation of photoactive components in non‐halogenated solvents (o‐Xylene and 2‐methyltetrahydrofuran (2‐MeTHF)), two bilayer‐processed photoactive films have been obtained via different solvent combinations (o‐Xylene/o‐Xylene for PM6 (o‐Xylene)/Y6C12 (o‐Xylene) and o‐Xylene/2‐MeTHF for PM6 (o‐Xylene)/Y6C12 (2‐MeTHF)). Different morphologies of bilayer‐processed photoactive films influence exciton dissociation and charge extraction properties of corresponding devices. Finally, the device hosting o‐Xylene/o‐Xylene processed photoactive film has a superior efficiency (10.6%) than the o‐Xylene/2‐MeTHF processed photoactive film‐based device (7.2%). Differently from device efficiency, the device based on o‐Xylene/2‐MeTHF processed photoactive film exhibits the preferable storage stability.